Close Examination of the Bar Removal Procedure: The Surgeons' Voice - Alvarez-Garcia, Natalia; Ardigo, Laura; Bellia-Munzon, Gaston; Martinez-Ferro, Marcelo (European Journal of Pediatric Surgery, 2018)
Introduction Complications of the Nuss procedure are well known. However, publications about intraoperative and postoperative complications of the bar removal procedure (BRP) are scarce. Are they uncommon, unknown, or underreported? Are we ready to face them?Objective This study aims to explore the profile of complications of the BRP, risk perception, and preventive actions undertaken by the Chest Wall International Group (CWIG) surgeons.Materials and Methods A 14-question online survey was posted to the members of the CWIG from February 1 to 28, 2016. A qualifying question was setup to ensure respondents performed Nuss' procedure/variations. Overall, 96.5% of respondents (n = 116) qualified.Results Despite being experts in the field of chest wall surgery 62.5% of respondents had performed ≤ 100 BRP and only 37.5% ≥ 100 BRP. Intraoperative complications: Severe bleeding from the bar tunnel was experienced at least one time by 28% of respondents and other serious complications, even death, were reported by 12%. Major surgical maneuvers to treat complications (sternotomy, thoracotomy, life-support maneuvers) were implemented by 62% of the surgeons who had experienced acute complications. Postoperative complications: Overall they were experienced at least once by 73.5% of surgeons. Wound seroma was the most cited complication (42%), followed by pneumothorax (27.5%). Surprisingly, one in every four surgeons acknowledged not requesting a routine chest X-ray before patient discharge. Complications versus experience: The report of acute complications increased with cumulative experience: Close to 50% for surgeons with < 100 BRP and as high as 100% for surgeons with > 1,000 BRP. Prevention of complications: Although 64% of surgeons defined the BRP as of intermediate/high risk, most of them (61%) do not prepare the operating room accordingly (availability of blood products, cardiac surgical backup, and perfusionist support).Conclusion BRP complications are being underestimated and underreported. Publications do not reflect the real spectrum of complications, which includes life-threatening conditions, even death. Preoperative planning and preparation of the operating room should not be disregarded.
Keywords: pectus excavatum; Nuss procedure; thoracic wall; minimally invasive surgery; complications